The Compressive Strength of High-Performance Concrete and Ultrahigh-Performance - E. H. Kadri; S. Aggoun; S. Kenai; A. Kaci (Advances in Materials Science and Engineering)
The compressive strength of silica fume concretes was investigated at low water-cementitious materials ratios with a naphthalene sulphonate superplasticizer. The results show that partial cement replacement up to 20% produce, higher compressive strengths than control concretes, nevertheless the strength gain is less than 15%. In this paper we propose a model to evaluate the compressive strength of silica fume concrete at any time. The model is related to the water-cementitious materials and silica-cement ratios. Taking into account the author's and other researchers’ experimental data, the accuracy of the proposed model is better than 5%.